2015
DOI: 10.1007/s12192-015-0579-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating heat shock protein 70 (HSPA1A) levels in gestational diabetes mellitus: a pilot study

Abstract: Recent data indicate that serum Hsp70 (HSPA1A) levels are increased in type 1 and 2 diabetes mellitus. However, there is no report in the literature on circulating Hsp70 levels in gestational diabetes mellitus. In this pilot study, we measured serum Hsp70 levels in 11 pregnant women with pregestational diabetes, 38 women with gestational diabetes, and 40 healthy pregnant women with ELISA. Plasma glucose levels, serum insulin concentrations, HbA1c values, and the Homeostatic Model Assessment-Insulin Resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 51 publications
0
20
0
1
Order By: Relevance
“…Our group has ventured certain ideas on the benefits of short periods of physiological stress improving blastocyst development rates and quality in bovine studies (Vajta et al, 2010). Perhaps vitrification provides a form of positive "sublethal" stress to embryos, and this idea is supported by a recent publication showing that Heat shock protein (Hsp 70) is elevated in gestational diabetes (Garamvölgyi et al, 2015). Such possibilities deserve exploration at a molecular level.…”
Section: Figurementioning
confidence: 99%
“…Our group has ventured certain ideas on the benefits of short periods of physiological stress improving blastocyst development rates and quality in bovine studies (Vajta et al, 2010). Perhaps vitrification provides a form of positive "sublethal" stress to embryos, and this idea is supported by a recent publication showing that Heat shock protein (Hsp 70) is elevated in gestational diabetes (Garamvölgyi et al, 2015). Such possibilities deserve exploration at a molecular level.…”
Section: Figurementioning
confidence: 99%
“…HSP70 is a stress‐induced protein involved in protein folding, degradation, and transport . A growing number of studies demonstrate that circulating HSP70 levels are elevated in diabetes mellitus types 1 and 2 and also in GDM . It has been suggested that inflammation and oxidative stress account for the increase in serum HSP70 concentrations in these disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Graphs represent significantly different proteins: A, collagen alpha-1 chain (col14A1); B, galectin-1 (GAL-1); C, heat shock protein 70 (HSP70) growing number of studies demonstrate that circulating HSP70 levels are elevated in diabetes mellitus types 1 and 2 and also in GDM. [20][21][22] It has been suggested that inflammation and oxidative stress account for the increase in serum HSP70 concentrations in these disorders. No data had been available to date on the possible effects of GDM on the placental expression of HSP70, and this is the first report of a higher abundance of this protein in the placenta of healthy controls than in women with GDM.…”
Section: Resultsmentioning
confidence: 99%
“…Recent data also showed that serum Hsp70 (HSPA1A) levels are elevated in diabetes mellitus types 1 and 2. However, further research is needed to determine whether Hsp70 is a cause in the pathogenesis of gestational diabetes [43].…”
Section: Situmorang and Ilyasmentioning
confidence: 99%